(untitled) (Research, Society and Development, 2020)
Objective: To identify the prevalence of prostate alteration types in the elderly, diagnosed by biopsy. Method and Materials: Cross-sectional and documentary research conducted between July and October 2016 on 230 medical records of the elderly who performed prostate biopsy in a public Pathology Laboratory in the West Region of Rio Grande do Sul. Year and type of change were analyzed as variables. Data were tabulated in Excel spreadsheet and submitted to statistical analysis. Results: The prevalence of benign prostatic hyperplasia was 123 (53%) and adenocarcinoma was 107 (46%). Conclusion: The prevalence of adenocarcionama increased in 2015, but in the period analyzed the largest number of cases are elderly people with Benign Prostatic Hyperplasia. It is noted the importance of performing of the diagnostic examination, given the high numbers of prostate alterations, and the need to development actions aimed at strengthening the National Policy for Integral Attention to Men’s Health.